MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT HARMONI NIRWANA LESTARI - Muhammad Jakarianto; Koesmawan Koesmawan; Teuku Ramli Zakaria (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2023)
This research aims to examine and analyze "The Influence of Work Motivation and Compensation on Employee Performance at PT. Harmoni Nirwana Lestari Jakarta." This type of research is quantitative. The data used in this study are primary data obtained from questionnaires distributed to employees at PT. Harmoni Nirwana Lestari Jakarta. The sample size used was 75 respondents. The data obtained were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests, and coefficient tests using the SPSS 24 program. The partial test results for work motivation significantly affect employee performance with a t-value of 8.404 and a significance level of 0.000. Compensation significantly affects employee performance with a t-value of 8.223 and a significance level of 0.000. Meanwhile, the simultaneous testing for work motivation and compensation significantly affects employee performance at PT. Harmoni Nirwana Lestari Jakarta with an F-value of 41.597 and a significance level of 0.000.